THE EFFECTIVENESS OF THE PROJECT METHOD IN TEACHING HUMANITARIAN DISCIPLINES - Stepanenko, Olena; Valentieva, Tatyana; Parfanovich, Ivanna; Svoboda, Ivo; Marukhovska-Kartunova, Olga (Revista EDaPECI : Educação a Distância e Práticas Educativas Comunicacionais e Interculturais, 2024)
Cutting-edge methodologies within higher education necessitate the cultivation of a proficient and competitive specialist capable of innovative thinking and can perform professionally amidst contemporary volatile circumstances. The purpose of this study was to identify the effectiveness of the project method as an innovative tool for the teaching of humanitarian subjects. The research used such methods as follows: questionnaire, observation, experiment, as well as statistical methods for data processing. In the course of the research, it was determined that the students who were engaged in the project activity, during the project, autonomously researched scientific, reference, educational, and methodological literature. A group of experts found that students’ participation in project activities influenced the development of creative activity and creative systemic thinking, contributed to their self-organization. During the survey, it was determined that students' independent work on creating projects ensures the development of personal and functional components of self-organization.The research's scientific novelty lies in its exclusive focus on students studying humanitarian disciplines. The restricted scope of the experiment facilitated the identifying the project approach as such that can be integrated into the academic system to enhance students' personal and practical proficiencies, thereby promoting their overall growth. Further research can be aimed at determining the effectiveness of using game methods in the course of teaching of humanitarian disciplines.